Membangun Kapasitas Pokdarwis: Pelatihan Pengelolaan Wisata Interaktif Dam Kembar yang Berkelanjutan di Desa Ajung - Zuama Al Amin, Muhammad; Hadits, Nurul; Maulani, Silvi; Adnan, Fahrobby (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Tourism is a potential sector that can drive local economic growth, especially in rural areas that are rich in natural and cultural beauty. Ajung Village, with ecotourism potential in the Twin Dam Tourism area, has formed a Pokdarwis (Tourism Awareness Group) to manage and develop the tourist destination. To support effective tourism management and promotion, training and capacity building for Pokdarwis was conducted, which included tourism management and the application of digital technology. The training activities included an introduction to the Widamar ecotourism concept, promotion strategies, and the use of technology such as websites and augmented reality. The results showed a significant increase in Pokdarwis' understanding, with the average post-test score increasing compared to the pre-test, indicating that the training was successful in improving Pokdarwis' knowledge and skills in tourism management and promotion. The implementation of digital technology in tourism promotion also provides added value in efforts to attract tourists to Ajung Village.